Experimental and Numerical Study of Cutting Force in End-Milling Operation Using Statistical Method - K., Kadirgama; M. M., Noor; M. M., Rahman; R. A., Bakar (2009)
The present paper explores the experimental and finite element study to predict the cutting force produced in end-milling operation for modified AISI P20 tool steel using statistical approach. The first order cutting force equations were developed utilizing the response surface methodology (RSM) to study the effect of input cutting parameters including the cutting speed, feed rate, radial depth and axial depth of cut. The explicit code was used to estimate the cutting and thrust forces. It can be seen that the longitudinal component of cutting force predicted by RMS and finite element analysis (FEA) are excellent agreement with the experimental results at 95% of confident interval. It can be observed that the range of the error for both methods within 10% except few and the more error occurred for higher cutting speed. At a level of confidence of 95%, the lack-of-fit F –value of 3.50 is not significant with relative to the pure error and zero order term and the model could fit and adequate. The acquired results show that the axial depth of cut, radial depth of cut and feed rate are strongly related with the cutting force. It can be seen that the increases of cutting force with increases of axial depth of cut, radial depth of cut and feed rate, however, the decreases of cutting speed. The cutting force obtained the highest value about 426 N at cutting speed 100m/min.